In-situ single chamber arc sputtering process for YCd0.3Ba2Cu3O7-? superconducting thin films - Yakinci, ME; Balci, Y; Aksan, MA; Aydogdu, Y; Ates, H (Kluwer Academic/Plenum Publ, 1999)
Superconducting YCd0.3Ba2Cu3O7-delta thin films have been deposited in-situ onto single crystal MgO substrates using a DC arc-sputtering process. The depositions were carried out in a single chamber deposition system equipped with two target holders. The films deposited at the optimum condition exhibited strong (001) orientation with a high peak: intensity. The best electrical properties were achieved to be 90 K for T-e, 81K for T-zero and the transport critical current density J(c) = 675 A/cm(2) at 77K and 2.3x10(3) A/cm(2) at 4.2 K for the sample deposited at the optimum conditions.
International Conference on Physics and Chemistry of Molecular and Oxide Superconductors (MOS-99) -- JUL 28-AUG 02, 1999 -- ROYAL INST TECHNOL, STOCKHOLM, SWEDEN